High Lithium Ion Transport Through rGO-Wrapped LiNi0.6Co0.2Mn0.2O2 Cathode Material for High-Rate Capable Lithium Ion Batteries - Ahn, Wook; Seo, Min-Ho; Pham, Tuan Kiet; Nguyen, Quoc Hung; Luu, Van Tung; Cho, Younghyun; Lee, Young-Woo; Cho, Namchul; Jeong, Soon-Ki (Frontiers in Chemistry, 2019)
In this work, we show an effective ultrasonication-assisted self-assembly method under surfactant solution for a high-rate capable rGO-wrapped LiNi0.6Co0.2Mn0.2O2 (Ni-rich cathode material) composite. Ultrasonication indicates the pulverization of the aggregated bulk material into primary nanoparticles, which is effectively beneficial for synthesizing a homogeneous wrapped composite with rGO. The cathode composite demonstrates a high initial capacity of 196.5 mAh/g and a stable capacity retention of 83% after 100 cycles at a current density of 20 mA/g. The high-rate capability shows 195 and 140 mAh/g at a current density of 50 and 500 mA/g, respectively. The high-rate capable performance is attributed to the rapid lithium ion diffusivity, which is confirmed by calculating the transformation kinetics of the lithium ion by galvanostatic intermittent titration technique (GITT) measurement. The lithium ion diffusion rate (DLi) of the rGO-wrapped LiNi0.6Co0.2Mn0.2O2 composite is ca. 20 times higher than that of lithium metal plating on anode during the charge procedure, and this is demonstrated by the high interconnection of LiNi0.6Co0.2Mn0.2O2 and conductive rGO sheets in the composite. The unique transformation kinetics of the cathode composite presented in this study is an unprecedented verification example of a high-rate capable Ni-rich cathode material wrapped by highly conductive rGO sheets.